Design and Performance Evaluation of an Off-Grid Solar Powered Automatic Aquarium Water Filling System 100 Wp - Mufti Ardi, Ardhe; Sunardi, Sunardi (Universitas Muhammadiyah Surakarta, 2026)
The increasing use of aquariums in household environments requires a reliable and automated water filling system to maintain stable water volume. In general, aquarium water filling systems still rely on electric pumps powered by the public electricity grid (PLN), which increases electricity consumption and may cause operational disruptions during power outages. This study aims to design and experimentally evaluate the performance of an automatic aquarium water filling system based on a 100 Wp off-grid photovoltaic (PV) power system. The proposed system consists of a 100 Wp solar panel, a pulse-width modulation (PWM) solar charge controller, a 12 V 20 Ah VRLA battery, a DC–AC inverter, a single-phase water pump, and a float switch–based water level sensor. The system design was carried out based on load analysis and component requirement calculations, followed by experimental testing under real operating conditions. Performance evaluation included measurements of photovoltaic output characteristics, battery charging behavior, inverter output stability, and water pump performance during the aquarium filling process. The experimental results show that the photovoltaic system produced an average operating voltage of 13.72 V under solar irradiance conditions of up to approximately 1,000 W/m2. The battery charging current ranged from 3.3 A to 6.3 A, with an average value of 5.9 A, and the battery voltage increased from 6.4 V to 12.6 V during the charging process. The inverter was able to maintain a relatively stable AC output voltage in the range of 232–234 V and supplied an average power of 36.9 W to the water pump during battery-powered operation. During aquarium filling tests, the water pump operated at a voltage range of 232–235 V with a current of 0.8–0.9 A and an electrical power range of 50.32–56.37 W. The system successfully filled a 90-liter aquarium with a filling time ranging from 12.85 to 18.01 minutes and a corresponding water flow rate of 5.00–6.71 L/min. These results demonstrate that a compact 100 Wp fully off-grid photovoltaic system integrated with battery energy storage, inverter-based AC operation, and float switch–based automatic control is capable of reliably supporting an automatic aquarium water filling process. This study provides experimental evidence that small-scale photovoltaic systems can serve as a practical and sustainable alternative energy source for household aquarium automation applications.